Constelações de aprendizagens na comunidade quilombola do Candói-PR - Souza, Osmir Marques (2021)
This dissertation aims to reflect on the learning processes experienced by the remaining quilombola community of Cavernoso 01 in the municipality of Candói - PR. The theoretical and methodological perspective is based on the concepts of learning constellations by Silva (2016;2017;2020) and the reflections of Fredrik Barth (2000) about ethnic cultural boundaries, allowing through the understanding of educational anthropology about the dynamics of Afro-Brazilian traditional knowledge. Specifically, we seek to understand, through bibliographic and field research, to what extent the learning processes are constituted and permeate through ethnic social groups, and how the learning constellations permeate the spaces of the present group. In this scenario of learning, the search for the bond with ancestry stands out in the relations of the quilombola community in learning with seniority, collectivity, matricentrality, and religiosity that form the elements of the constellation, whose dynamics establish the time and learning experience for each member. Through ethnography, the importance of women's participation was perceived, especially as a condition of their belonging and access to community knowledge for the development of their ancestral bond.